Deconstructing the Marginalization of Women in the Story of Prophet Lot: A Hermeneutic Analysis of Ma’na cum Maghza - Rifqatul Husna; Nabila Safa Nirmala; Salih Abdulrahman Alsounusi (UAS PRESS, 2026)
Textual readings of the Qur’anic story of Prophet Lot, particularly QS. Hud (11): 78-79, have often concentrated on sexual deviance and divine punishment while leaving insufficient attention to how female figures are represented. This interpretive tendency creates an academic and ethical problem: the phrase “these are my daughters” is frequently read without adequate linguistic, historical, and socio-moral contextualization, allowing women to appear as objects of negotiation rather than as moral subjects. Previous studies on the Lot narrative have largely examined disaster, punishment, and moral deviation, whereas the gendered implications of androcentric exegesis remain underexplored. This study therefore aims to deconstruct the marginalization of women in the story of Prophet Lot and to recover the Qur’an’s ethical message through the Ma’na cum Maghza approach. This research employs a qualitative library-based method by analyzing Qur’anic verses, classical tafsir works, and contemporary gender-hermeneutical literature. The analysis proceeds through three stages: ma’na tarikhi, the reconstruction of the verse’s historical-linguistic meaning; maghza tarikhi, the identification of the Qur’an’s original moral significance in its historical context; and maghza mutaharrik, the contextual development of that significance for contemporary gender justice. The findings show that women’s marginalization does not originate from the Qur’anic text itself but from patriarchal interpretive frames that neglect context and ethical purpose. The Lot narrative primarily criticizes violence, coercion, bodily exploitation, and unjust social relations; consequently, it supports a more humane and gender-equitable Qur’anic interpretation.